2018
DOI: 10.1007/978-981-13-1247-2_15
|View full text |Cite
|
Sign up to set email alerts
|

Making the P T $$\mathbb {PT}$$ Symmetry Unbreakable

Abstract: It is well known that typical PT -symmetric systems suffer symmetry breaking when the strength of the gain-loss terms, i.e., the coefficient in front of the non-Hermitian part of the underlying Hamiltonian, exceeds a certain critical value. In this article, we present a summary of recently published and newly produced results which demonstrate various possibilities of extending the PT symmetry to arbitrarily large values of the gain-loss coefficient. First, we recapitulate the analysis which demonstrates a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…(1), above which the PT symmetry breaks down [6,7]. Nevertheless, examples of systems with unbreakable PT symmetry are known too [8]. In fact, the linearized version * Electronic address: zyyan@mmrc.iss.ac.cn of the model introduced in the present work also avoids the breakdown, see Eqs.…”
Section: Introduction and The Modelmentioning
confidence: 92%
“…(1), above which the PT symmetry breaks down [6,7]. Nevertheless, examples of systems with unbreakable PT symmetry are known too [8]. In fact, the linearized version * Electronic address: zyyan@mmrc.iss.ac.cn of the model introduced in the present work also avoids the breakdown, see Eqs.…”
Section: Introduction and The Modelmentioning
confidence: 92%
“…The stability of the stationary states was identified by numerical computation of eigenvalues of small perturbations, using linearized equations (41) for perturbations around the stationary solitons. Finally, the stability predictions, produced by the eigenvalues, were verified by simulations of the perturbed evolution of the solitons (some technical details are reported elsewhere [63]).…”
Section: Numerical Results For Zero-vorticity Solitonsmentioning
confidence: 99%
“…Solitons are also vulnerable to destabilization via the PT -symmetry breaking at the critical value of the gain-loss coefficient [59]. Nevertheless, it was found that, in some settings, the solitons' PT symmetry can be made unbreakable, extending to arbitrarily large values of the strength of the model's imaginary potential [60]- [62], see also a brief review of the unbreakability concept in [63]. The particular property of these models is that self-trapping of solitons is provided not by the self-focusing sign of the nonlinearity, but by the defocusing sign, with the coefficient in front of the cubic term growing fast enough from the center to periphery.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, PT -symmetric Hamiltonians may admit transformation into Hermitian ones [12,13]. A well-established fact is that the spectrum of Hamiltonians with complex potentials subject to constraint (1) is real below a critical strength of the imaginary part of the potential, at which the PT symmetry gets broken, making the system unstable [14] (exceptions in the form of models with unbreakable PT symmetry are known too [15]). Thus far, the PT symmetry was not directly realized in quantum systems with complex potentials.…”
Section: Introductionmentioning
confidence: 99%
“…The PT symmetry in an optical waveguide (as well as its CP counterpart) may naturally combine with the material Kerr nonlinearity, giving rise to propagation models based on cubic nonlinear Schrödinger equations (NLSEs) with the complex potentials subject to condition (1). These models may generate PT -symmetric solitons, which were addressed in many theoretical works [18], [23]- [59], [15] (see also reviews [41,42]), and experimentally demonstrated too [34]. Although the presence of the gain and loss makes PT -symmetric media dissipative, solitons exist in them in continuous families, similar to the commonly known situation in conservative models [43], while usual dissipative solitons exist as isolated solutions (attractors, if they are stable) [44].…”
Section: Introductionmentioning
confidence: 99%